U.S. economic policy towards China under the Biden administration - Zaharul Abdullah; Rosyidah Muhamad; Noor Ashikin Said (Penerbit Universiti Kebangsaan Malaysia, 2024)
Since the inception of the open-door policy in 1978, China has progressively become more integrated into the global economy through trade, foreign direct investment, and, more recently, outward direct investment. This economic integration has gained momentum with initiatives like the ‘Go Global’ strategy, China’s entry into the World Trade Organization (WTO) in 2001, and the launch of the Belt and Road Initiative in 2013. China’s economic ascent, coupled with its increasing political influence and military power, prompted the United States (US) to initiate a strategy of rebalancing in the Asia Pacific region, starting with the Bush administration and continuing through the Obama, Trump, and Biden administrations. During the Trump administration, this rebalancing strategy was supported by decoupling strategy, ultimately leading to a trade war with China. Despite its intention to avoid the initiation of a new Cold War and to adopt a more moderate stance towards China, the US-China trade war has evolved further into a tech war under the Biden administration. Given this context, this article aims to outline the primary characteristics of the US economic policy towards China during the Biden administration, comparing it to the Trump administration and assessing its impact on both nations. The central argument of this article is that the primary characteristics of the US economic policy towards China under Biden administration are rebalancing and decoupling, carried over from the policies of the preceding Trump administration, and there are clear signs that these characteristics are deepening. Furthermore, the article demonstrates that the extensive decoupling measures enacted by the US have proven effective in diminishing China’s role in global industrial and supply chains, particularly in industries related to semiconductors and chipmaking equipment.